My old lady - Benchetrit, Nitsa; Barrot, David C.; Horovitz, Rachael; Foster, Gary, 1961-; Horovitz, Israel; Kline, Kevin; Smith, Maggie, 1934-; Scott-Thomas, Kristin, 1960-; Freiss, Stephane; Pinon, Dominique, 1955-; Groodt, Stephane de.; Amathieu, Michel; et al. (Universal City, CA Universal Studios Home Entertainment, 2015)
When Mathias arrives at the sumptuous Parisian apartment he inherited from his father, he's surprised that the property comes with two stubborn live-in tenants who are not required to leave according to an ancient French real estate law. Unable to sell the place, Mathias moves in with the feisty Englishwoman Mathilde and her daughter, Chloe. But as Mathias and Chloe draw increasingly closer, Mathilde unveils a complex labyrinth of secrets that unites the trio in unexpected ways.
Based on the play by Israel Horovitz.
DVD release of the 2014 motion picture.
Bonus feature: 92nd Street Y Annette Insdorf interview with Kevin Kline and Israel Horovitz.
Director of photography, Michel Amathieu ; editors, Jacob Craycroft, Stephanie Ahn ; music, Mark Orton.
Kevin Kline, Maggie Smith, Kristin Scott Thomas, Stephane Freiss, Dominique Pinon, Stephane de Groodt.
Rating: PG-13; for thematic material and some sexual references.
Keywords: Roommates -- Drama; Family secrets -- Drama; Paris (France) -- Drama; France -- Paris; DVD-Video discs; Comedy films; Feature films; Fiction films; Drama; Film adaptations